Effects of isokinetic muscle strengthening on muscle strength, mobility, and gait in post-stroke patients: a systematic review and meta-analysis - Alves, Iura Gonzalez Nogueira (2018)
Objective:To investigate whether isokinetic muscle strengthening improves muscle strength, mobility, and gait in post-stroke patients. Methods: We searched for randomized controlled trials at PubMed/Medline, SciELO, PEDro, and Cochrane Central Register of Controlled Trials, from the earliest date available to June 2018. Randomized controlled trials that examined the effects of isokinetic muscle strengthening versus other rehabilitation interventions or control in post-stroke patients were included. Study quality was evaluated using the PEDro scale. Weighted mean difference (WMD) and 95% confidence intervals (CIs) were calculated, and heterogeneity was assessed using the I2 test. Results: In total, 13 studies (347 patients) focusing on the use of isokinetic in rehabilitation following stroke were included. All trials were of low-to-moderate quality. Isokinetic muscle strengthening improved muscle strength WMD 0.8 (95% CI: 0.2, 1.4; N = 96), mobility WMD −2.03 seconds (95% CI: −2.9, −1.1; N = 111) and gait speed WMD 0.9 m/s (95% CI: 0.05, 1.8; N = 87). Conclusion: Isokinetic muscle strengthening seems to be a useful strategy for improving muscle strength, mobility, and gait in post-stroke patients.